PENERAPAN METODE SAS (STRUKTURAL, ANALITIK, SINTETIK) DALAM MENINGKATKAN PEMBELAJARAN BAHASA ARAB DI MTS NASYRIL ISLAM 14 ULU PALEMBANG - Maulida, Nadia; Ridho, Yusuf; Wasilah, Wasilah; Sabana, Rendi; Nazarmanto, Nazarmanto (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Arabic is a vital language in the Islamic world as it is the language of the Qur'an and a primary source of Islamic sciences. However, the teaching of Arabic at the Madrasah Tsanawiyah level in Indonesia still faces challenges, especially in students’ reading and writing skills. This study aims to explore the implementation and effectiveness of the SAS (Structural, Analytic, Synthetic) method in improving Arabic learning at MTs Nasyril Islam 14 Ulu Palembang. Employing a sequential exploratory mixed methods approach, the study involved 30 seventh-grade students as subjects. Data were collected through observation, interviews, documentation, and pre-test/post-test. The findings reveal a significant improvement in students’ Arabic reading and writing abilities after the SAS method was applied. The average post-test score (80.16) was higher than the pre-test (74.83), supported by statistical tests showing a significant difference. This indicates the SAS method's effectiveness in enhancing student engagement and achievement in Arabic learning.